Android Personnel Monitoring Location Pada Institusi Kepolisian Berbasis Web - Afrizal, Afrizal; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: The prominent responsibilities of police are to taking care and serving society, thus the working sphere become a common job done by personnel of police. Each of personnel has rights and responsibilities that is clearly managed, including the schedule management of their duties. However, from this point forward, the personnel job is less in getting the monitor from the leader or the officer. This case causes an obstacle of the institution, in which it is the lack of communication of personnel in doing the coordination of serving the society and the occurring of personnel indiscipline that leaves the duty location. Solution to fill the above requirement is the development of system an Android Personnel Monitoring Location in Police Institution of Web-Based. This system consists of android mobile application and the website that are connected to the same database. This system can be worth for monitoring and finding the place of every personnel in real time, so that it can be easily to coordinate the personnel as well.